2021
DOI: 10.1177/19714009211012358
|View full text |Cite
|
Sign up to set email alerts
|

An international bibliometric study of scientific articles on intracranial aneurysms

Abstract: Objectives The number of original scientific researches on intracranial aneurysms has risen over the last 30 years. Despite the rise in the number of articles, there is no up-to-date exhaustive bibliometric research in the literature. This study aimed to contribute to the literature via a bibliometric analysis of the original scientific researches on intracranial aneurysms published over the last 30 years. Methods The literature review was done using the Web of Science. All articles and its citations containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…The reason why the WoS database is preferred is that Wos indexes the articles published in journals with higher impact factors than the other databases and comprehensive citation analyzes can be performed (10). In recent years, WoS has been preferred more in bibliometric analyzes (7)(8)(9)(10)(11)(12)(13). Additionally, if more than one database is used, the same articles in different databases can be included in the analysis more than once, therefore reliability can decrease.…”
Section: Co-citation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why the WoS database is preferred is that Wos indexes the articles published in journals with higher impact factors than the other databases and comprehensive citation analyzes can be performed (10). In recent years, WoS has been preferred more in bibliometric analyzes (7)(8)(9)(10)(11)(12)(13). Additionally, if more than one database is used, the same articles in different databases can be included in the analysis more than once, therefore reliability can decrease.…”
Section: Co-citation Analysismentioning
confidence: 99%
“…Bibliometric is the analysis of scientific outputs in the literature using various statistical methods (5,6). In parallel with the increasing number of publications in the literature, bibliometric research and analyzes have been carried out on different medical subjects (5)(6)(7)(8)(9)(10)(11)(12). Bibliometric studies can reveal past and current trends on a topic using citation analysis, bibliometric and statistical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The application of bibliometric analysis in the field of IA is fruitful. To be specific, Kiraz et al ( 5 ) explored the papers related to IA from 1980 to 2020 analyzed by VOSviewer, with the research area limited to the category “neuroscience and neurology” and the search item “aneurysm” in the title, which excluded numerous IA-focused publications. Lu et al ( 6 ) elaborated on the characteristics, content, and changes of the most prominent unruptured IA from the 100 most cited articles.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Thanks to bibliometric research, the most active authors, journals, institutions, countries and the most cited influential studies on a subject or a field are revealed. 9 15 With the increase in the number of publications in the literature, studies based on statistical and bibliometric analysis have been carried out on many important medical issues, especially in recent years. 9 15 …”
Section: Introductionmentioning
confidence: 99%
“… 9 15 With the increase in the number of publications in the literature, studies based on statistical and bibliometric analysis have been carried out on many important medical issues, especially in recent years. 9 15 …”
Section: Introductionmentioning
confidence: 99%